al-Maṭbūʻāt al-ʻUmānīyah fī al-Munaẓẓamāt al-Duwalīyah: Iṣdārāt al-Lajnah al-Waṭanīyah al-ʻUmānīyah lil-Tarbiyah wa-al-Thaqāfah wa-al-ʻUlūm, Tajribatan wa-Namūdhajan - Nawfalī, Ḥumayd ibn Sayf (al-Muʼtamar al-Duwalī al-Khāmis bi-Mālīziyā: Ḥarakat al-Ṭibāʻah al-ʻUmānīyah wa-Atharuhā fī al-Tawāṣul al-Ḥaḍārī, 2018)
Nations have sought to communicate with one another since antiquity, and in the present age ways have emerged that affirm such communication by varied means, among them the movement of publications of every kind, whether individual or institutional. An example is the publications of the Omani National Commission for Education, Culture and Science, issued in both Arabic and English, which have succeeded to a considerable degree in making Oman known in international forums and have carried its heritage and culture to all the countries of the world through their counterpart national commissions in those countries, besides being available on international platforms. This paper, presented within the conference theme on the role of governmental institutions in publishing the Omani heritage, treats that experience as an instructive model.
MHF-PRINT2018-024
Keywords: Omani National Commission; UNESCO; International organisations; Cultural diplomacy; Publications; Oman